The Application of Virtual Characters for Education on Social Media - Lin, Jun (2022)
The main aim of the thesis is to determine the effectiveness and efficiency of implementing virtual characters in education on social media. As social media carries the characteristics of persistence, visibility, spreadability, and searchability, it can be an excellent tool for e-learning. Different categories of social media platforms also provide various opportunities for educators to perform non-traditional teacher methods. However, there are a few limitations when it comes to education on social media. One of them is that visual presentation can be a key factor in attracting more students. Thus, the thesis suggests that virtual characters can be a solution to improve the visual aspect of online learning. The main reason is that virtual characters are on the rise in popularity in recent years around the world, so it is reasonable to consider the inclusion of such technology in virtual learning. A controlled experiment of posting two types of educational videos, one with a virtual character while the other does not, on social media is conducted. After analyzing the performance data between the two types of videos, it is found that virtual characters are more effective in getting more viewers. However, there is no hard proof that showcases the effectiveness of virtual characters in getting students to be more engaged in the online learning process.